Ethylamine as new derivatization reagent differentiating reducing from non-reducing saccharides - Schwack, Wolfgang; Heilmann, Danny; Morlock, Gertrud E.; Justus Liebig University Giessen (My University, 2023)
Typical derivatization reagents for saccharides in high-performance thin-layer chromatography, like 2-naphthol sulfuric acid, aniline diphenylamine orthophosphoric acid, or p-aminobenzoic acid, generally detect both reducing and non-reducing saccharides. A new reagent was found with ethylamine, specifically reacting with reducing saccharides on normal-phase silica gel plates, resulting in strongly fluorescent zones after heating the plate at 150 °C for 15 min. In contrast, non-reducing saccharides generally did not reveal fluorescent signals tested with 26 different saccharides. Optimal chromatographic separation was achieved with a mixture of 2-propyl acetate, methanol, and water with 1 mg/mL natural product reagent A when the plate was twofold developed. The high sensitivity of the ethylamine derivatization was shown with mean limits of detection and quantification of 10 and 30 ng per zone, respectively, calculated by different methods for selected mono- and disaccharides. The developed method has exemplarily been used for the digestion control of starch by α-amylase, the determination of lactose in lactose-free milk, and for the quantitative and qualitative study of honey. The analysis of honey gave an excellent example of the advantageous consecutive derivatization with ethylamine and aniline diphenylamine orthophosphoric acid reagent as reagent sequence to detect the coelution of reducing and non-reducing saccharides.